2020
DOI: 10.3390/jcm9051266
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence for Q10 Coenzyme Supplementation in Heart Failure: From Energetics to Functional Improvement

Abstract: Oxidative stress and mitochondrial dysfunction are hallmarks of heart failure (HF). Coenzyme Q10 (CoQ10) is a vitamin-like organic compound widely expressed in humans as ubiquinol (reduced form) and ubiquinone (oxidized form). CoQ10 plays a key role in electron transport in oxidative phosphorylation of mitochondria. CoQ10 acts as a potent antioxidant, membrane stabilizer and cofactor in the production of adenosine triphosphate by oxidative phosphorylation, inhibiting the oxidation of proteins and DNA. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 93 publications
0
35
0
3
Order By: Relevance
“…Coenzyme Q (CoQ) plays a crucial role in the production of mitochondrial energy and reactive oxygen. CoQ is considered to be an antioxidant, and lack of it can lead to an increase in mitochondrial reactive oxygen species [ 16 ]. This could suggest that AAAs have mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme Q (CoQ) plays a crucial role in the production of mitochondrial energy and reactive oxygen. CoQ is considered to be an antioxidant, and lack of it can lead to an increase in mitochondrial reactive oxygen species [ 16 ]. This could suggest that AAAs have mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…CoQ 10 deficiency is associated with several diseases, such as cardiovascular diseases, muscular dystrophy and neurodegenerative disorders ( 87 ). Administration of CoQ 10 as a supplement along with standard clinical therapy shows positive effects in patients with hypertension ( 87 ) and heart failure ( 89 ). Higher plasma CoQ 10 concentrations in patients with MI lead to improved left ventricular function.…”
Section: Current Developments In Mitochondria-targeted Agents Withmentioning
confidence: 99%
“…Aside from LDLR, the other members of this family are less well studied specifically for lipoprotein transport at the BBB, and could be a fruitful avenue for future studies to improve CoQ 10 retention by the brain. In addition, the use of LDLR inhibitors may also have potential therapeutic value as a means of increasing cellular CoQ 10 levels in other patient groups which have been associated with a deficiency in the level of this isoprenoid, such as those with cardiovascular disease [ 75 ]. However, further studies will be required before this can be confirmed or refuted.…”
Section: Discussionmentioning
confidence: 99%